A policy portfolio approach to plastics throughout their life cycle: Supranational and national regulation in the European Union - Sandra Eckert; Orr Karassin; Yves Steinebach (Environmental Policy and Governance, 2024)
The environmental and health problems caused by plastics throughout their life cycle have attracted considerable public attention over the past decade, triggering policy responses in many constituencies. Similarly, interdisciplinary research on plastics has been burgeoning in the past few years, and political science contributions have covered the manifold root causes and consequences of this shift in public policy including media coverage, evolving discourses and policy agendas. In view of this policy relevance that drives scholarly inquiry, it is surprising that we lack a systematic assessment of the actual policy outputs. This article fills this lacuna by developing a policy portfolio approach to plastic regulation. To illustrate and substantiate our approach, we provide an exploratory analysis of EU plastics regulation over the last twenty years, complementing this with Denmark, Germany, and Poland as diverse cases of member state regulation. Overall, our research shows that the number of policy measures targeting plastics has massively increased both at the supranational and national level. This policy growth, however, varies across policy targets and instruments. Our findings highlight first, that the policy targets addressed are mainly located at the end of the plastics life cycle; and second, that the instrument choice is privileging the use of hierarchical forms of intervention over the use of market- or information-based instruments. We discuss these features of the policy portfolio approach in light of existing research on plastics and life-cycle-oriented policy approaches such as the Circular Economy.
Keywords: 330; European Union; life cycle; plastics; policy instruments; policy portfolio